A new diminutive species of Allobates Zimmermann and Zimmermann, 1988 (Anura, Aromobatidae) from the northwestern Rio Madeira—Rio Tapajós interfluve, Amazonas, Brazil - Simões, Pedro Ivo; Sturaro, Marcelo José; Peloso, Pedro Luís Vieira; Lima, Albertina P. (Zootaxa, 2013)
We describe Allobates grillisimilis from the northwestern region of the Rio Madeira—Rio Tapajós interfluve, state of Am-azonas, Brazil. The new taxon is characterized by its small snout-to-vent length (12.8–16.0 mm, the smallest among known Allobates), by the color pattern of adults (surfaces of throat, chest and abdomen unpigmented), by morphological traits of larvae (a single row of very elongate papillae on posterior labium), and by its distinctive advertisement call, formed by trills of short pulses emitted in a variable number. We also provide notes on reproductive behavior of the new species.